Effects of the dynamics of departmental labor income on access to the Private Pension Administration System - Saldaña Pacheco, Luis Arnaldo (2022)
Objective: To determine the effect of the dynamic of departmental labor income in Peru on the affiliation to the Private Pension Administration System (SPP), in the period 2004-2021. Method: A panel data model with fixed effects was used to estimate the effect of the dynamics of labor income during the 2004-2021 period, understood as the proportion of the Economically Active Population (EAP) that has dependent labor income above the minimum wage (RMV), on an access indicator such as the affiliation to the SPP referred to the percentage of the EAP that is affiliated to said system. Results: There is a differentiated dynamic in the rate of affiliation to the SPP and in the growth of labor income, and the dependent labor income between the departments. Likewise, a positive and statistically significant effect of the proportion of the EAP that has dependent labor income above the minimum wage on the percentage of affiliation to the SPP was determined. Conclusion: The departments whose population has a higher proportion of dependent labor income above the minimum wage have a greater access to the SPP, understood as a higher level of affiliation as part of the EAP.